(untitled) (Eurasian Research Bulletin, 2024)
This article explores the concept of architectural ecology in the context of Samarkand, a city renowned for its historical significance and architectural heritage. It discusses the importance of integrating ecological principles into urban development strategies to preserve the city’s unique identity while addressing contemporary environmental challenges. The article reviews relevant literature, analyzes current urban development trends in Samarkand, proposes methods for incorporating ecological design principles, and discusses the potential benefits and challenges. The article concludes with recommendations for sustainable urban development in Samarkand